Caesarean scar-unusual site of ectopic pregnancy: a rare case report - Kharode, Amruta; Chaudhari, Kamlesh; Inamdar, Saunitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Scar ectopic pregnancy is the rarest type of ectopic pregnancy; however, it is becoming more common around the world. It is a life-threatening condition caused by abnormal embryo implantation in the myometrium and fibrous tissue of the prior scar after a caesarean section, hysterotomy, myomectomy, or metroplasty. With a better understanding of the disease and an increased rate of caesarean section, there is a significant increase in this condition. Early and correct diagnosis, combined with prompt treatment, can help to avoid pregnancy problems including haemorrhage and uterine rupture, as well as preserve fertility.